Existence of Performing Rights: An Analysis of Implications and Orientations for Café Singers - Prayogi, Akhwan; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Performing rights are rights attached to copyright as an integral part of the creation of a work. In the context of copyrights to songs or music, performing rights relate to the need to pay royalties to songwriters or music for attempts to use songs or music commercially.Purposes of the Research: Implications of performing rights for café singers to continue paying royalties based on statutory regulations and how the performing rights orientation for café singers is ideal in ensuring justice for songwriters or music as well as for café singers.Methods of the Research: Normative legal research with a concept and statutory approach.Results of the Research: The implications of performing rights for café singers to continue paying royalties based on statutory regulations, namely that there is no legal certainty for café singers because there is no specific regulation governing them. The performing rights orientation for café singers is ideal in ensuring justice, namely by excluding royalty payments for café singers because the commercialization impact received by café singers is not large and only sufficient to make ends meet.